La responsabilidad social, más allá de la gestión de la calidad en los gobiernos locales de Colombia (2012)
Implementing a model of quality management whether ISO 9001 or NTCGP 1000, develops the institutional capacity to understand and respond consistently to the expectations of an interested party such as customers, very important for any organization. It raises the possibility that these capabilities can be used to manage an organization’s relationships with its other interested parties, such as those arising in the Guide to Social Responsibility GTC 180, under a perspective which views social responsibility as an extended frontier of quality management.This research explores the possibilities for linking the quality management system implemented in Colombian municipalities of Valle del Cauca under the NTCGP 1000 model and the Colombian GTP 180 model for social responsibility, based on skills developed in the implementation of the quality management system.We used the descriptive research method of determining the principles, elements, and practices that may contribute to the articulation and can facilitate the implementation of social responsibility in the municipalities, based on the identification of the elements of convergence, divergence and complementarities in the approaches of these two standards.We determined the perception of the internal and external population of the municipalities included in the study, for information on how the quality management system operates and on their knowledge of various aspects of social responsibility.Finally we developed a methodology for the implementation of social responsibility based on the GCT 180 guide in municipalities that have implemented a quality management system based on NTCGP 1000.